Wireless Network Visualization in 3D Virtual Environment Framework - Sulaiman, Hamzah Asyrani; Othman, Mohd Azlishah; Ismail, Mohd Muzafar; Misran, Mohamad Harris (2012)
Simulating a signal propagation of wireless cognitive network has been widely accepted by researchers in order to come out with three-dimensional (3D) representation data display. Instead of using primitive way to understand the behavior of signal propagation, 3D visualization of wireless networking could also help researchers to study the limitation and exploration of wireless cognitive network deeply. In this paper, we would like to address the requirement and the potential of using 3D representation to visualize properly the wireless cognitive network. We also performed preliminary test of our 3D visualization system using OpenGL graphic library to visualize the propagation of signal travelling in specific room with several medium. The test has been conducted in order to understand the requirement of wireless cognitive network in 3D visualization before the actual system is built.